Emergence of transient intersegmental plane by pulmonary circulation single-blocking: is it the true intersegmental plane?. (11th August 2021) - Chen, Liang; Li, Qingshu; Chen, Xu; Ge, Mingjian
Abstract: We report the transient intersegmental plane formed by circulation single-blocking, which is consistent with the true intersegmental plane, and its formation principles, characteristics and potential applications. Abstract : We reported the circulation single-blocking method for identifying the intersegmental plane during segmentectomy [1], in which as the artery or vein of the target segment was resected and lung expanded completely, a clear inflation–deflation demarcation was observed after several min.